Development and Characterization of Hydroxyapatite Coatings with a Biomimetic Plate-like Morphology - Elena Ungureanu; Diana Maria Vranceanu; Alina Vladescu (Dragomir); Irina Titorencu; Anca Constantina Parau; Vasile Pruna; Cosmin Mihai Cotrut (Proceedings)
Introduction. Modern medicine depends on biomaterials. Thus, it is imperative that these materials continue to be developed and improved. Methods. This work aimed at designing hydroxyapatite-based coatings (HAp) with high osseointegration properties by developing a biomimetic morphology that resembles that of natural HAp found in bone tissue. The biomimetic HAp coatings with plate-like morphology were successfully obtained using the pulsed galvanostatic electrochemical approach on pure Ti discs. The coatings were investigated in terms of surface morphology, chemical and phasic composition, in vitro bioactivity, and cell interaction. Results and Discussion. The morphological investigations revealed that using electrochemical deposition, HAp-based coatings with very thin and wide plate-like crystals can be obtained. The chemical composition highlighted that both Ca and P are present, and that the Ca/P ratio registered values of 1.66, being close to that of the stoichiometric HAp of 1.67. The phasic composition analysis showed that the main phase consisted of hydroxyapatite (ICDD #09-0432), with a crystallinity of ~25%. The biomineralization ability of the cp-Ti substrate was improved by the HAp-based coatings, reaching a maximum value of 9.7 mg after 3 weeks of immersion in simulated body fluid (SBF) compared to the Ti samples which gained a mass of only 0.3 mg after the same period. The in vitro experiments using human mesenchymal stem cells demonstrated that the HAp-based coatings enhanced the extracellular matrix, the intracellular deposition of Ca, and cell viability when compared to the cp-Ti substrate, demonstrating the advantages of the developed coatings. Conclusions. Therefore, the outcomes confirm that coatings with improved and adjustable properties can be designed for medical applications by using the electrochemical deposition technique.